PENGARUH BRAINGYM TERHADAP PENINGKATAN KECAKAPAN BERHITUNG SISWA SEKOLAH DASAR - Prihastuti UNAIR (Jurnal Cakrawala Pendidikan, 2009)
This study aimed to investigate the influence of the BrainGym on the improvement of the numerical skills of Year 3 students of elementary school. The research subjects consisted of 40 Year 3 students out of 43 students of SD Percobaan 2 Depok, Sleman Regency, Yogyakarta. Three students were not included in the study because they were absent when the posttest was administered. The instrument to collect the data on students numerical skills was an informal assessment instrument in the form of an inventory developed by the teacher. The inventory was a numerical skill test, consisting of 10 items and a checklist to obtain information on the use of the BrainGym. The data analysis showed that there was a significant difference in the means of the numerical skill test before and after the BrainGym treatment (ttest = - 2.772; p = 0.008). The mean after the treatment (Mposttest = 12.67) was higher than that before the treatment (Mpretest = 11.70). It was concluded that the BrainGym treatment was effective to improve the score of the numerical skills of Year 3 students of elementary school. The evaluation of the BrainGym movements showed that they were easy and fun. The students felt that they were more relaxed and comfortable, and did not have tensions and boredom so that they kept motivated. The classroom atmosphere was more lively and dynamic, and the students felt fresher and managed to think clearly. Keywords: BrainGym, numerical skills